1986 y-Walk participants stretching - Unknown:::Creator::::::::::::
Negative shows a large group of men and women who are participants in the 1986 y-Walk. They are probably in the YWCA's parking lot and they are doing stretches as a group. Most of them are bending over as if to touch their toes in this picture. A few balloons can be seen among the crowd.